Immunization of mice by a multimeric L2-based linear epitope (17-36) from HPV type 16/18 induced cross reactive neutralizing antibodies - Farhad Motavalli Khiavi; Arash Arashkia; Maryam Nasimi; Mehdi Mahdavi; Majid Golkar; Farzin Roohvand; Kayhan Azadmanesh (Wolters Kluwer Medknow Publications, 2017)
Current licensed and commercially available prophylactic human papillomavirus (HPV) vaccines (Cervarix and quadrivalent/nine valents Gardasil) are based on major capsid protein L1 virus-like particles (VLPs) production which are expensive and type specific. Minor capsid L2-RG1 linear epitope (17-36) is a known candidate for induction of cross-neutralizing antibodies to develop low-cost pan-HPV vaccines. Herein, we report construction and expression of a three tandem repeats of L2-RG1 derived from HPV16 and 18 fused with the same head to tail pattern (HPV16:17-36×3+ HPV18:17-36×3; hereafter termed dual-type fusion L2 peptide) in E. coli and provide the results of its immunogenicity in mice. SDS-PAGE and western blot analyses indicated proper expression of the peptide that could be further purified by Ni-NTA affinity chromatography via the located C-terminal 6xHis-tag. Mice immunized by formulation of the purified peptide and Freund adjuvant raised neutralizing antibodies which showed proper cross reactivity to HPV L2 (11-200) of types: 18, 16, 31 and 45 (which totally are responsible for 90% of cervical cancers) and efficiently neutralized HPV18/16 pseudoviruses in vitro. Our results imply the possibility of development of a simple, low-cost preventive HPV vaccine based on this dual-type fusion L2 peptide in bacterial expression system with broad spectrum.